Toward a phenomenology of terrorism: implications for research and policy - Morris, Travis (Crime, law and social change, 2011)
The central theme of this paper is that the phenomenology of perception can contribute to conceptualizing terrorism, in terms of both a research orientation and policy applications. This means that counter-terrorism needs to be grounded in a holistic perspective that has meaning from the point of view of those engaged in terrorism. A critique of the "war on terror" counter-terrorism practices is followed by a discussion of phenomenology and its implications for a holistic perception of counter-terrorism. Four cases are presented that show how a phenomenological approach can facilitate counter-terrorism study and policy.